Trends in child labor and the impact on health in adulthood in Brazil from 1998 to 2008 - Marislei Nishijima; André Portela Fernandes de Souza; Flávia Mori Sarti (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2015)
There is little evidence in Brazil on the impact of child labor on health status in adulthood. This study aimed to investigate trends in child labor in Brazil and estimate the long-term effects of child labor on the health of Brazilian adults, using nationally representative databases (Brazilian National Household Sample Survey) from three different years (1998, 2003, and 2008). The models were based on a two-stage linear equation and Generalized Method of Moments (GMM). The results suggest that child labor has declined in Brazil, although the data still show patterns of early entry into the country's labor market. Regardless of the type of work, child labor adversely affected health outcomes in adulthood, both directly (impacts on health outcomes) and indirectly (losses in educational attainment). Child labor places a long-term burden on Brazilians, jeopardizing the formation of human capital through negative impacts on health outcomes in adulthood.